A longitudinal study of social support and educational attainment of Mexican American and White non-Hispanic adolescent mothers - Woodall, Renée Andrade, author; Chavez, Ernest, advisor; Bloom, Larry, committee member; Viney, Wayne, committee member; Yang, Ray, committee member (Colorado State University. Libraries, 2004)
This study assessed social support and educational attainment of pregnant and parenting adolescent females. Pregnant Mexican American (n = 42) and White non-Hispanic (n = 12) adolescents completed the Hispanic Dropout Survey (Chavez and Oetting, 1986). Social support from parents and friends were analyzed at Time 1, when the adolescents were pregnant, and at Time 2, when most adolescents were parenting. Educational outcomes were measured at Time 2. Results were compared to non-pregnant Mexican American (n = 480) and White non-Hispanic (n = 268) adolescents who completed the same measure. Participants who had been pregnant at Time 1 reported less perceived support from parents and friends or a special person at Time 2 than females who were not pregnant at Time 1. Mexican American females perceived less support from friends or a special person than White non-Hispanic females at Time 2. Adolescent mothers were just as likely to be currently enrolled in high school, to have graduated from high school, to have a G.E.D., and to have attended postsecondary schools as other adolescent females. Results were discussed with regard to helping adolescent mothers feel supported and be successful in pursuing an education.
Keywords: psychotherapy; families and family life; personal relationships; sociology; individual and family studies; clinical psychology